An approach to secure EPUB ebook content - Faniband, Yunus Parvej; Nandyal, Aslam; Ishak, Iskandar; Sidi, Fatimah; A. Jabar, Marzanah (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
EPUB is an industry standard e-book format. Digital content owners and producers use Digital Rights Management (DRM) to protect and regulate the mechanism of distribution and usage of those digital assets. The features of content protection may range from limiting simple copying or transferring the content, and enabling reading to an authorized reader hardware/software, to complex enterprise distribution policies involving user and device authentication for a specific duration. Commercial E-Publishing services offer to help authors to self-publish or distribute their eBooks with DRM on agreed royalty terms. These E-Publishing services mandate extensive guidelines and procedures to make the content readable and use a proprietary format with DRM. Since International Digital Publishing Forum (IDPF) has no standardized algorithm for copyright protection of EPUB, there is a challenge to secure the EPUB content following the copyright recommendations. In this paper, we present an overview of the proposed EPUB Content protection and control system and explain a mechanism to protect the EPUB content in a cross-platform open source EPUB editor. We have implemented a prototype of the system using the ‘Sigil‘ EPUB authoring tool.